Analisis Biaya Standar Pada Industri Tempe UD. Bang Dhin di Kabupaten Bireuen - Murni Murni (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This study aims to determine and analyze calculations in determining production costs in the UD Tempe industry. Bang Dhin Bireuen District with a study that is a standard cost analysis. Research on standard cost analysis has been done by researchers before, but it has a different object from this study. Previous research took objects in manufacturing industries such as the furniture industry, this research is a descriptive qualitative research with the object of research is the UD Tempe Industry. Bang Dhin, Bireuen District, Aceh Province. Data sources in this study are primary data and secondary data. Primary data were obtained through direct interviews with respondents while secondary data were obtained through literature review. Collection techniques are carried out through documentation, observation and interviews. Analysis of standard costing data on UD. Bang Din Tempe Bireuen Regency based on the results of interviews shows that there is no standard price determination for raw materials used in the production process, but only has a standard quantity of raw materials. Standard raw material prices are based on the average price of raw materials directly from sellers on the market.